Installation of a Neuromate Robot for Stereotactic Surgery: Efforts to Conform to Japanese Specifications and an Approach for Clinical Use—Technical Notes - KAJITA, Yasukazu (Neurol Med Chir (Tokyo), 2015)
The neuromate is a commercially available, image-guided robotic system for use in stereotactic surgery and is employed in Europe and North America. In June 2015, this device was approved in accordance with the Pharmaceutical Affairs Law in Japan. The neuromate can be specified to a wide range of stereotactic procedures in Japan. The stereotactic X-ray system, developed by a Japanese manufacturer, is normally attached to the operating table that provides lateral and anteroposterior images to verify the positions of the recording electrodes. The neuromate is designed to be used with the patient in the supine position on a flat operating table. In Japan, deep brain stimulation surgery is widely performed with the patient's head positioned upward so as to minimize cerebrospinal fluid leakage. The robot base where the patient's head is fixed has an adaptation for a tilted head position (by 25 degrees) to accommodate the operating table at proper angle to hold the patient's upper body. After these modifications, the accuracy of neuromate localization was examined on a computed tomography phantom preparation, showing that the root mean square error was 0.12 ± 0.10 mm. In our hospital, robotic surgeries, such as those using the Da Vinci system or neuromate, require operative guidelines directed by the Medical Risk Management Office and Biomedical Research and Innovation Office. These guidelines include directions for use, procedural manuals, and training courses.